A calculation method of sliding friction coefficient on tooth surface for helical gear pair based on loaded tooth contact analysis and elastohydrodynamic lubrication theory. (August 2021) - Wang, Cheng; Ken, Mao
The sliding friction coefficient on tooth surface is related to power loss, carry capacity and transmission performance of gear. Reasonable transmission analysis of gear pair is the premise of accurate calculation of sliding friction coefficient on tooth surface. However, for helical gear pair, the line contact without considering machining error/installation error/modification of gear is usually adopted to replace the major axis of ellipse caused by contact load. Therefore, in this paper, contact path on tooth surface, length of contact line, load distribution on tooth surface and loaded transmission errors are accurately calculated by loaded tooth contact analysis (LTCA). Combing with elastohydrodynamic lubrication (EHL) theory, a calculation method of sliding friction coefficient on tooth surface for helical gear pair is proposed.